2011
DOI: 10.5902/198346593069
|View full text |Cite
|
Sign up to set email alerts
|

Brand Relationships on Retailing: The Impact of Image on Behavioral Intentions of Consumers

Abstract: The electronics retail market has been growing in a remarkable way. On the other hand, the strong competition in retail and the fact that the same retailers sell products of similar brands and models, poses asignificant challenge for its differentiation. That's the purpose of this work, which aims at proposing a scale that measures these retailers' image, identifying the factors that impacted this image the most, as well as verifying the possible impacts of the image in the consumers' behavioral intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
2
1
0
Order By: Relevance
“…The results of this research showed that image positively influences patient loyalty. This finding supports the previous researches, such as Ryu et al (2012); Brandão et al (2011); Meng et al (2011) and Sumaedi et al (2014c). Hence, it can be stated that any increase in the image of healthcare service institution will result in the increase of patient loyalty.…”
Section: Theoretical Implicationsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this research showed that image positively influences patient loyalty. This finding supports the previous researches, such as Ryu et al (2012); Brandão et al (2011); Meng et al (2011) and Sumaedi et al (2014c). Hence, it can be stated that any increase in the image of healthcare service institution will result in the increase of patient loyalty.…”
Section: Theoretical Implicationsupporting
confidence: 91%
“…Chen and Tsai (2007) confirmed the positive impact of image on loyalty. The finding is also supported by other researchers, such as Ryu et al (2012); Brandão et al (2011); Meng et al (2011) and Sumaedi et al (2014c). Hence, it is expected that the similar condition is also found in the healthcare service context.…”
Section: Imagesupporting
confidence: 85%
“…On other contexts than public transport services, some researchers have found the positive impact of image on a construct relates with intention to reuse, namely customer loyalty (e.g. Chen and Tsai, 2007;Ryu et al, 2012;Brandao et al, 2011;Meng et al, 2011). On the context of public transport services, Sumaedi et al (2014a) have tested the impact of image on public transport passengers' behavioral intention, which is a construct that relates with intention to reuse.…”
Section: Imagementioning
confidence: 99%